2001
DOI: 10.1007/bf03016586
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose dexamethasone effectively prevents postoperative nausea and vomiting after ambulatory laparoscopic surgery

Abstract: Prophylactic iv dexamethasone 5 mg significantly reduces the incidence of PONV in women undergoing ambulatory laparoscopic tubal ligation. At this dose, dexamethasone is more effective than metoclopramide 10 mg or placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 25 publications
2
30
0
2
Order By: Relevance
“…These results suggest that dexamethasone 2.5 mg represents the minimum effective dose for the prevention of PONV after major gynecological surgery. In a study by Huang et al, 23 the incidence of PONV was reduced by about 35% after pretreatment with a low dose of dexamethasone (5 mg) in patients undergoing laparoscopy for tubal ligation.…”
Section: Objectif : La Combinaison De Médicaments Antiémétiques Pourrmentioning
confidence: 96%
“…These results suggest that dexamethasone 2.5 mg represents the minimum effective dose for the prevention of PONV after major gynecological surgery. In a study by Huang et al, 23 the incidence of PONV was reduced by about 35% after pretreatment with a low dose of dexamethasone (5 mg) in patients undergoing laparoscopy for tubal ligation.…”
Section: Objectif : La Combinaison De Médicaments Antiémétiques Pourrmentioning
confidence: 96%
“…Meta-analysis of new double-blind RCTs comparing metoclopramide (10 mg) with placebo controls report no statistically significant differences in nausea and vomiting in the immediate postoperative period (Category A1-E evidence), but indicate efficacy in the reduction of vomiting during the first 24-h postoperative period (Category A1-B evidence). 14,18,23,[41][42][43][44] Statistically significant differences were reported in the original Guidelines for nausea and vomiting without indicating time of measurement (Category A1-B evidence). Scopolamine.…”
Section: A1-e Evidence)mentioning
confidence: 99%
“…Meta-analyses of new double-blind RCTs comparing dexamethasone with placebo controls corroborate findings reported in the original Guidelines indicating that this antiemetic is effective in the prophylaxis of postoperative vomiting and reduced use of rescue antiemetics, and for the prophylaxis of nausea when higher doses are administered (Category A1-B evidence). 8,12,24,26,29,36,37,39,41,43,44,[47][48][49][50][51][52][53][54][55][56] The consultants and ASA members agree that the pharmacologic prophylaxis of nausea and vomiting improves patient comfort and satisfaction, reduces time to discharge, and should be done selectively. Multiple Pharmacologic Agents for Prophylaxis of Nausea and Vomiting.…”
Section: A1-e Evidence)mentioning
confidence: 99%
“…[2,3,17,[20][21][22][23][24][25][26] Henzi et al analysed 17 studies comparing the efficacy of prophylactic Dexamethasone with a placebo for PONV, and found it more effective than placebo. [27] Conversely, Fujii et al conducted a study in women undergoing major gynaecological operations, and found that Dexamethasone at 8 mg dose alone did not reduce PONV.…”
Section: Discussionmentioning
confidence: 99%